Large tumoral calcinosis and pathological femur fracture in a hemodialysis patient with secondary hyperparathyroidism - Liu, Xiwei; Hong, Song; Chen, Ganjun; Tu, Chongqi (International Surgery Journal, 2016)
Tumoral Calcinosis (TC) is a rare complication of uremic patients on dialysis. Bone erosion or fracture rarely happens in TC patients. TC is easy to be misdiagnosed as a malignant bone tumor by inexperienced orthopedists. We report the clinical, radiological and magnetic resonance imaging findings in a rare case of large TC which caused femur erosion both and fracture in a 49-year-old woman with uremia and secondary hyperparathyroidism (HPT) on hemodialysis and describe the surgical treatment and pathology results.